Emerging Directions in Embedded and Ubiquitous Computing: EUC 2007 Workshops: TRUST, WSOC, NCUS, UUWSN, USN, ESO, and SECUBIQ, Taipei, Taiwan, December 1-4, 2007, Proceedings - Denko, Mieso K; Shih, Chi-Sheng; Li, Kuan-Ching; Tsao, Shiao-Li; Zeng, Qing-An; Park, Soo-Hyun; Ko, Young-Bae; Hung, Shih-Hao; Park, Jong Hyuk; Denko, Mieso (Lecture Notes in Computer Science, 2007)
This book constitutes the refereed proceedings of the EUC 2007 workshops held in conjunction with the IFIP International Conference on Embedded and Ubiquitous Computing, EUC 2007, in Taipei, Taiwan, in December 2007. The 69 revised full papers presented together with four invited papers were carefully reviewed and selected from about 200 submissions to the seven workshops. A broad range of topics are covered.